Neuroimaging studies in obsessive compulsive disorder [Obsesif Kompulsif Bozuklukta Beyin Görüntüleme Çalişmalari] - (:unkn) unknown (My University, 2003)
Neuroimaging studies have advanced the understanding of obsessive-compulsive disorder (OCD), by revealing the evidence for structural or functional deviations as in many other psychiatric disorders. This article provides an updated review in neuroimaging studies in OCD published to date. Recent computerised brain tomography (CT), magnetic resonance imaging (MRI) studies, single photon emission computerised tomography (SPECT), and positron emission tomography (PET) studies were reviewed. Although many lines of evidence point to an abnormal development of basal ganglia in a group of OCD patients, many questions remain unanswered. SPECT studies provided us a strong evidence of cortical perfusion increase and perfusion abnormalities in basal ganglia in OCD. During PET studies, an increase in metabolism in the orbitofrontal cortex, anterior cingulate, caudat nucleus, and thalamus was noted and with the pharmacological treatment, metabolism in the right orbitofrontal cortex and right caudate nucleus returned to their normal levels. The results of the structural and the functional brain imaging studies showed us that there are evidence of abnormalities in orbitofrontal cortex, anterior cingulate cortex, caudate nucleus, basal ganglia, and thalamus in OCD patients. Neuroimaging studies are helpful in determining the brain structure and their functions related to OCD as well as revealing the pathophysiology of this particular disorder.
Keywords: Frontal-subcortical circuitry; Neuroimaging studies; Obsessive-compulsive disorder